2012
DOI: 10.1021/cg301256g
|View full text |Cite
|
Sign up to set email alerts
|

A Series of New Three-Dimensional d–f Heterometallic Coordination Polymers with Rare 10-ConnectedbctNet Topology Based on Planar Hexanuclear Heterometallic Second Building Units

Abstract: A series of new three-dimensional (3D) d−f heterometallic coordination polymers, namely, [LnM(μ 5 -PyIDC)(μ 2 -INIC)(μ 3 -INIC)]•x-H 2 O [Ln = Sm, M = Co, x = 3 (1); Ln = Sm, M = Ni, x = 1 (2); Ln = Eu, M = Co, x = 3 (3); Ln = Eu, M = Cd, x = 3 (4); Ln = Eu, M = Zn, x = 3 (5); Ln = Gd, M = Co, x = 3 (6); Ln = Gd, M = Cd, x = 3 (7); Ln = Tb, M = Co, x = 3 (8); Ln = Tb, M = Cd, x = 2 (9); Ln = Tb, M = Zn, x = 3 (10); H 3 PyIDC = 2-(pyridine-3-yl)-1H-4,5-imidazoledicarboxylic acid; HINIC = isonicotinic acid], hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 75 publications
0
22
0
Order By: Relevance
“…It can be seen that the correlation emission band of the ligand is in the range of 390–550 nm, and the strongest emission peak is at 423 nm. The weak broad bands from 390 to 550 nm may be due to ligand–metal charge transfer (LMCT) from the Pzdc 2– ligand to the Zn 2+ ion , . The characteristic emission peaks of the Sm III ion indicate that energy can be efficiently transferred from the Pzdc 2– ligand to the Sm 3+ ion.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen that the correlation emission band of the ligand is in the range of 390–550 nm, and the strongest emission peak is at 423 nm. The weak broad bands from 390 to 550 nm may be due to ligand–metal charge transfer (LMCT) from the Pzdc 2– ligand to the Zn 2+ ion , . The characteristic emission peaks of the Sm III ion indicate that energy can be efficiently transferred from the Pzdc 2– ligand to the Sm 3+ ion.…”
Section: Resultsmentioning
confidence: 99%
“…Yield 15% (based on the Zn). Elemental analysis Calculated (%) for C 24 (2). A mixture of HIPT (10.6 mg, 0.05 mmol), Zn(OAc) 2 ·2H 2 O (10.9 mg, 0.05 mmol), 2-propyl-1 h-imidazole-4,5-dicarboxyacid (H 3 PrIDC, 9.9 mg, 0.05 mmol), and distilled water (6 mL) was sealed in a 10-mL Teflon-lined stainless steel autoclave, and HCl (1 M/L) was used to adjust the pH at 3-6.…”
Section: Materials and Instrumentationmentioning
confidence: 99%
“…Only a few CPs based on HIPT were reported [15][16][17][18][19][20][21][22]. Incorporation of more types of metal ions or organic ligands into a single unique framework is worth studying because the functionality of CPs is mainly derived from metal ions and ligands [23,24]. The combination of nitrogen donor ligands and aromatic carboxylate has been proven to be an effective strategy for constructing diverse mixed-ligand CPs [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Encouraged by these productive findings, many research groups have focused on the coordination features of various functionalized H 3 IDC ligands in recent years. Indeed, H 3 IDC derivatives with diverse substituent groups at the 2‐position of the imidazole ring, including nonaromatic groups and aromatic groups, have been widely used as effective building blocks for the construction of new CPs.…”
Section: Introductionmentioning
confidence: 99%
“…Our group, among others, has recently designed and synthesized several analogue ligands of H 3 IDC, such as 2‐hydroxymethyl‐1 H ‐imidazole‐4,5‐dicarboxylic acid (H 4 hmIDC), 2‐trifluoromethyl‐1 H ‐4,5‐imidazole dicarboxylic acid (H 3 TFMIDC),, 2‐pyridyl‐4,5‐imidazole‐dicarboxylic acid (H 3 PyIDC), and so on, to build up diverse CPs. It has been found that the introduced substituent groups not only may induce spatial effects on the adjacent carboxylate groups, but also can provide additional coordination sites, leading to the construction of a series of new CPs.…”
Section: Introductionmentioning
confidence: 99%